(Invited) Displacement Damage and Single Event Effects in AlGaN/GaN HEMTs. (5th January 2017) - Koehler, Andrew D.; Anderson, Travis J; Khachatrian, Ani; Roche, Nicolas J.-H.; Buchner, Stephen; Weaver, Brad D; Hobart, Karl D; Kub, Francis J
Abstract : High-energy (2 MeV) protons at various fluences, up to 6 x 10 14 H + /cm 2 were used to investigate the impact of displacement damage on AlGaN/GaN HEMTs. A reduction in the maximum drain current is observed, which is attributed to a decrease in the two-dimensional electron gas (2DEG) mobility and sheet carrier density. In addition, a nondestructive focused pulsed-laser technique is used to investigate single event effects in the GaN HEMT devices, both before and after proton irradiation. Characteristics such as the peak amplitude, width, and total charge collected are investigated at various bias conditions and at different locations in the GaN HEMTs. The maximum charge collected is identified to be at the location corresponding to the peak electric field within the device. Defects within the GaN HEMTs induced by proton irradiation increase the time constant of the single event decay.